Android-Based Elderly Health App Analysis in Indonesia - Trisfa Augia; Hendery Dahlan (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The increasing of the number of elderlies in Indonesia is a demographic bonus that needs an attention both their health and well-being. Physiological limitations and spaces do not make this age group unable to receive any information about their health. With the advancement of technology, they also can access information and communication technology facilities such as applications on android devices. This led to the development of applications for elderly health in Indonesia. The purpose of this study is to screen the number of android-based elderly applications in Indonesia, knowing the characteristics of android-based elderly applications, and the quality of applications. This study used descriptive methods through screening and analysis of android-based elderly applications in Indonesia in Play Store® during February to March 2022. Screening is conducted using the keywords